2019
DOI: 10.3390/brainsci9070172
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of IL-1 Receptor Antagonist in a Mouse Model of Migraine

Abstract: Migraine is a disorder characterized by attacks of monolateral headaches, often accompanied by nausea, vomiting, and photophobia. Around 30% of patients also report aura symptoms. The cause of the aura is believed to be related to the cortical spreading depression (CSD), a wave of neuronal and glial depolarization originating in the occipital cortex, followed by temporary neuronal silencing. During a migraine attack, increased expression of inflammatory mediators, along with a decrease in the expression of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…We also studied the possible diagnostic and prognostic value of TSPAN32 expression in PBMC of MS patients, on the course of the disease. The use of whole-genome expression databases has been largely exploited [25][26][27][28] for the characterization of pathogenic pathways and to identify therapeutic targets for a variety of disorders, including immunoinflammatory and autoimmune diseases [29][30][31][32][33][34][35][36], cancer [37][38][39], and has allowed dismantling pathogenetic pathways [40][41][42], along with the identification of novel tailored therapeutic targets [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…We also studied the possible diagnostic and prognostic value of TSPAN32 expression in PBMC of MS patients, on the course of the disease. The use of whole-genome expression databases has been largely exploited [25][26][27][28] for the characterization of pathogenic pathways and to identify therapeutic targets for a variety of disorders, including immunoinflammatory and autoimmune diseases [29][30][31][32][33][34][35][36], cancer [37][38][39], and has allowed dismantling pathogenetic pathways [40][41][42], along with the identification of novel tailored therapeutic targets [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also evaluated the transcriptomic analysis of MIF, DDT and their receptors in the brains of a mouse model of alcoholism. This analysis was carried out by DNA microarray analysis that represents a useful in silico toll for the better understanding of pathogenic pathways and the possible prediction of new diagnostic therapeutic approaches in several clinical settings, including immunoinflammatory and autoimmune diseases and fibrotic diseases (45,46,(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). Our analysis first demonstrated that no differences in the expression of MIF, DDT and their receptors can be found in brains of both rodent models of AUD and patients with this condition.…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, this is the first meta-analysis to be performed exclusively on studies performed on a specific brain region from SCZ subjects and controls, rather than on studies encompassing different Brodmann areas or brain anatomical structures. The use of whole-genome expression databases has been largely exploited by our group and others [37][38][39][40][41] for the characterization of pathogenic pathways and to identify therapeutic targets for a variety of disorders, such as autoimmune diseases [42][43][44][45][46][47][48][49][50], cancer [44,51,52], and has allowed researchers to characterize pathogenic pathways [53][54][55][56], and potential therapeutic targets [57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%